Strengthening Food Security of Jember District Throug Commodity-Added Value Analysis Soybean in Agroindustry “Saudara Jaya” - Rachmat Udhi Prabowo; Sinta Tri Wahyuni (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Palu, 2025)
One of the development successes is in the agricultural sector related to food commodities. Food crops are one of the farming subsectors that have an important role in the Indonesian economy, such as providing added value for commodities that get treatment (agro-industry). An example of added value is making agricultural products as new products that are long-lived and ready for consumption. The added value generated can increase revenue. One of the farming subsectors that gets a lot of treatment (processing) is food commodities such as soybeans. Soybeans can be consumed directly or in processed form. Soybeans in processed form can be used as, tempeh, soy sauce, milk, sauce, and so on. is a snack made from soybeans and consumed as a companion to rice. Gebang Village is one of the villages in Patrang District, Jember Regency which has many agro-industries, one of which is